Infinite country ebook A novel. - Engel, Patricia (2021)
A REESE'S BOOK CLUB PICK and INSTANT NEW YORK TIMES BESTSELLER WINNER OF THE 2021 NEW AMERICAN VOICES AWARD, LONGLISTED FOR THE 2022 ANDREW CARNEGIE MEDAL , A 2022 DAYTON LITERARY PEACE PRIZE FINALIST , AND A NATIONAL ENDOWMENT OF THE ARTS "BIG READS" SELECTION "A profound, beautiful novel." — People * "Poignant." — BuzzFeed * "A breathtaking story of the unimaginable prices paid for a better life." — Esquire This "heartbreaking portrait of a family dealing with the realities of migration and separation" ( Time ) is "a sweeping love story and tragic drama [and] an authentic vision of what the American Dream looks like in a nationalistic country" ( Elle ). I often wonder if we are living the wrong life in the wrong country. Talia is being held at a correctional facility for adolescent girls in the forested mountains of Colombia after committing an impulsive act of violence that may or may not have been warranted. She urgently needs to get out and get back home to Bogotá, where her father and a plane ticket to the United States are waiting for her. If she misses her flight, she might also miss her chance to finally be reunited with her family. How this family came to occupy two different countries, two different worlds, comes into focus like twists of a kaleidoscope. We see Talia's parents, Mauro and Elena, fall in love in a market stall as teenagers against a backdrop of civil war and social unrest. We see them leave Bogotá with their firstborn, Karina, in pursuit of safety and opportunity in the United States on a temporary visa, and we see the births of two more children, Nando and Talia, on American soil. We witness the decisions and indecisions that lead to Mauro's deportation and the family's splintering—the costs they've all been living with ever since. Award-winning, internationally acclaimed author Patricia Engel, herself a dual citizen and the daughter of Colombian immigrants, gives voice to all five family members as they navigate the particulars of their respective circumstances. Rich with Bogotá urban life, steeped in Andean myth, and tense with the daily reality of the undocumented in America, Infinite Country "is as much an all-American story as it is a global one" ( Booklist , starred review).